Overlord. Dark legend. - Codemasters (Firm) (University City, CA : Codemasters, 2009)
Once upon a time, a new Overlord was born into malevolence and chaos. Use your Wii remote to guide our brave young hero and his loyal band of Minions through this epic, twisted fairytale. Get ready to unleash your dark side.
Title from container.
ESRB rating: T, teen (alcohol reference, fantasy violence).
System requirements: Nintendo Wii.
105182
Keywords: Computer adventure games; Nintendo Wii video games